Portfolio Assessment at Featured Schools in Yogyakarta - Rahdiani, Dian; Ramadhan, Aditya; Prakoso, Bagus Hary (Indonesian Journal of Educational Assessment, 2020)
Assessment is part of the learning cycle, so that assessment cannot be separated from a learning activity. The Minister of Education and Culture said that the implementation of the 2020 National-Based School Examination will be carried out with exams held by schools. The exam is conducted to assess student competence and can be done in the form of a written test or a comprehensive assessment such as portfolios and assignments. This portfolio can later be done through group assignments, paper work, and so on. Researchers want to know the extent of school readiness, teachers' perceptions and knowledge of portfolio assessments, types / forms of portfolio assessments that have been carried out in schools, and constraints in implementing portfolio assessments. The research was carried out in superior junior high junior high schools in the the Special Region of Yogyakarta, namely SMPN 1 Bantul and SMPN 4 Pakem. The implementation of the portfolio assessment carried out at SMPN 1 Bantul and SMPN 4 Pakem went very well and was effective because it was supported by school members (school principals, educators, education staff, students, parents, and the community) through various policies and concrete actions carried out consistently and the seriousness of the school in supporting the program.